Diaphragmatic Endometriosis: Review of the Literature and First Case of Robot-Assisted Laparoscopic Treatment. Issue 4 (October 2014) - Cela, Vito; Simi, Giovanna; Obino, Maria Elena Rosa; Uccelli, Alessia; D'Isidoro, Cristiano; Morelli, Luca; Pluchino, Nicola; Freschi, Letizia
Background: Thoracic endometriosis is a rare disorder affecting women in reproductive age. The etiopathogenesis of this disease is not well understood. The symptoms appear, but not necessarily, during periods in person affected by the condition. Methods: A 35-year-old woman came to our clinic, the Infertility and Assisted Reproduction Center of the University of Pisa, for infertility treatment. She described a clinical history of abdominal pain with irradiation up to the right shoulder, depending on her breathing or position, during menstruation. She also reported that she did not experience these symptoms while taking an oral contraceptive. Pelvic ultrasound examination and thorax X-ray were normal. The patient also underwent thoracic and abdominal pelvis magnetic resonance imaging (MRI). Thoracic MRI revealed a nodule on the right hemidiaphragm. It was decided to perform surgical removal of the nodule. Robotic-assisted surgery was used because of its multiple advantages in comparison with laparoscopic surgery, such as a 3-dimensional view, a decrease in surgeon fatigue and tremors, and an increase of wrist motion with improved dexterity and greater surgical precision. The surgery was performed in May 2012. The patient was put on the left lateral bedside. Pneumoperitoneum with CO2 was established with an intra-abdominal pressure of 12 mm Hg using a Veress needle. Robotic trocars of 8-mm diameter were introduced at the diaphragmatic level and connected to the robot arms. Her pelvic and abdominal organs appeared healthy. The right hemidiaphragm presented adherence with the liver due to endometriosis disease. We removed the adhesion, and we performed the excision of the diaphragmatic endometriotic nodule. The nodule was extracted through an endobag. Operative time lasted 2 hours. Conclusions: The postoperative evolution was satisfactory, and the patient left the hospital on the third postoperative day. No complications occurred. We showed that this approach is feasible and safe, without conversion to laparotomy.